Access to treatment for substance-using women in the Republic of Georgia: Socio-cultural and structural barriers - Otiashvili, David (2013)
BACKGROUND: In the Republic of Georgia, women comprise under 2% of patients in substance use treatment and to date there has been no empirical research to investigate what factors may facilitate or hinder their help-seeking behavior or access to treatment services. METHODS: This study included secondary analysis of in-depth interviews with 55 substance-using women and 34 providers of health-related services. RESULTS: The roles and norms of women in Georgian society were identified as major factors influencing their help-seeking behavior. Factors that had a negative impact on use of drug treatment services included an absence of gender-specific services, judgmental attitudes of service providers, the cost of treatment and a punitive legal position in regard to substance use. Having a substance-using partner served as an additional factor inhibiting a woman’s willingness to seek assistance. CONCLUSIONS: Within the context of orthodox Georgian society, low self-esteem, combined with severe family and social stigma play a critical role in creating barriers to the use of both general health and substance-use-treatment services for women. Education of the public, including policy makers and health care providers is urgently needed to focus on addiction as a treatable medical illness. The need for more women-centered services is also critical to the provision of effective treatment for substance-using women.